2019
DOI: 10.1108/pm-07-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate student satisfaction in the UK

Abstract: Purpose The purpose of this paper is to identify the relative importance of factors that influence the overall satisfaction of postgraduate built environment students and also examine the extent to which demographic backgrounds affect this. Design/methodology/approach The data used in this paper have been collected through Postgraduate Taught Experience Survey in the UK. Descriptive and statistical analysis methods were used to analyse student satisfaction variables and identify the extent to which demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Again, most of the currently available studies that centre on postgraduate studies are mainly focused on developed economies (Bright & Graham, 2016;Poon, 2019). Hofstede's theory suggested that there are differences in economies due to differences in culture which affect the value of their institutional culture and strategy (Hofstede, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Again, most of the currently available studies that centre on postgraduate studies are mainly focused on developed economies (Bright & Graham, 2016;Poon, 2019). Hofstede's theory suggested that there are differences in economies due to differences in culture which affect the value of their institutional culture and strategy (Hofstede, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…(2018:3) and Parahoo, Santally, Rajabalee and Harvey (2016) shows that competent or excellent students are those are intrinsically motivated to learn, synthesize and connect with diverse materials. In addition, Poon (2018) states that highly motivated students perform better than those who are not, as motivated students have adaptive attitudes and strategies, such as maintaining intrinsic interest, goal setting, and self-monitoring…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2018), Parahoo et. al., (2016 and Poon (2018), the following hypothesis is formulated: H3: Student motivation has a great positive effect on student performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientific literature lists a variety of factors that predict student satisfaction, including the quality of the teaching–learning process [ 6 , 73 , 74 , 75 ], as well as aspects related to the educational infrastructure, such as administrative staff [ 73 , 76 , 77 , 78 ], university facilities [ 65 , 79 , 80 , 81 ], location [ 65 , 78 ] and technological resources [ 66 ]. In this sense, educational technology should be highlighted as an important factor that influences student satisfaction, both with the educational infrastructure through the availability of technological resources and the support of information technologies [ 66 ], and with the teaching–learning process, by means of the use of technological resources by teachers [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some studies highlight the influence of gender on satisfaction with the teaching–learning process, although with contradictory results [ 74 , 86 ]. In this way, while Poon’s [ 74 ] research carried out on university students in the United Kingdom, revealed that women showed a lower level of satisfaction with the teaching–learning process than men, in O’Driscoll’s [ 86 ] research with Irish university students, they did not find statistically significant differences based on gender. Even other research has shown that these gender differences could be mediated by the use of a deeper learning approach and the age of university students [ 61 ].…”
Section: Introductionmentioning
confidence: 99%